Tokamak Configurations with Average Magnetic Well for Trapped Particles - Ohkawa, Tihiro (Kakuyūgō kenkyū, 1988)
A tokamak configuration which may have a reduced trapped particle turbulence level is proposed. The horizontal elongation with the triangularity opposite to the D-shape produces a comet-like cross section.